Avaliação do perfil imunomodulador do nitrato de cério incorporado em resinas acrílicas termopolimerizáveis sobre leucócitos humanos - Leite, Priscilla Kelly Batista da Silva (2017)
Introduction: Numerous researches have been developed in order to improve the mechanical, physical, antimicrobial and biocompatibility characteristics of acrylic poly (methyl methacrylate) (PMMA) resins used for prosthesis based on the incorporation of biomaterials. Cerium nitrate has application in the treatment of burns and has an antimicrobial effect, even against C. albicans. A new therapeutic strategy for prosthetic stomatitis, based on the incorporation of a biomaterial is relevant for clinical practice. In this context, the immunomodulatory activity of cerium nitrate incorporated into the resins has not been investigated yet. Aim: to evaluate, in vitro, the biocompatibility and immunomodulation of cerium nitrate incorporated in thermopolymerizable acrylic resins on leukocytes isolated from human blood. Method: Cytotoxicity was assessed using alamarBlue® on human PBMC isolated from the blood through the Ficoll Paque protocol. The data were tabulated through the Kruskal Wallis test with Tukey post hoc. Results: The viability of PBMC in the presence of cerium nitrate solution was shown to be dose-dependent (3250 μL / ml - 98.55% and 6500 μL / ml - 16.61%). In the presence of the test specimens, the cellular viability of PBMC was not observed at the incorporated concentrations studied compared to the control group. Conclusion: The isolated solution of cerium nitrate did not show cytotoxicity against PBMC cells up to 3250 μg / mL. When incorporated in thermopolymerizable acrylic resin, it did not present cytotoxicity to PBMC isolated from human blood at the two concentrations studied (16xCIM and 32xCIM).